Body weight unloading modifications on frontal plane joint moments, impulses and Center of Pressure during overground gait. (November 2016) - Fischer, Arielle G.; Wolf, Alon
Abstract: Background: Body weight unloading is a common method of gait rehabilitation. However, little is known about its effects on the overground gait biomechanical parameters which were often confounded by the walking modality (treadmill) or the speed variability when subjects walked overground while having to pull the body weight unloading system to which they were attached. By designing a mechanical device that pulled the system at a constant speed, we were able to assess the unique effects of body weight unloading on healthy subjects' kinetics during overground gait. Methods: Fifteen healthy subjects walked overground under three (0%, 15%, and 30%) body weight unloading experimental conditions. Kinetic measures included hip and knee frontal plane moments and impulses and the foot center of pressure. Findings: A significant inverse relationship was shown between increased body weight unloading levels (0% to 30%) and a decrease in the hip and knee first adduction moments and impulses and an increase in the lateral shift of the foot center of pressure. Frontal plane hip and knee kinetic curvature patterns remained similar as evidenced by low normalized RMSE under paired comparisons of the experimental conditions. Interpretation: Overground gait with up to 30% body weight unloading stands out as an efficient method of reducing loads on joints without distorting kinetic gait curvature patterns. The relationship between increased unloading with decreased hip and knee moments and impulses and increased lateral shift of the center of pressure also suggests that this shift may be an important diagnostic tool in gait assessment and correction. Highlights: Evaluate the effects of body weight unloading on gait kinetic biomechanical parameters Control the interaction of treadmill gait and body weight unloading by studying overground gait Unloading decreased hip and knee frontal plane kinetic parameters with similar curvatures Increased unloading caused a significantly increased lateral shift in the foot center of pressure Overground gait with body weight unloading advocates potential applications in gait reeducation